2019
DOI: 10.1007/s10664-019-09726-5
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparison of text-based mobile apps similarity measurement techniques

Abstract: Context Code-free software similarity detection techniques have been used to support different software engineering tasks, including clustering mobile applications (apps). The way of measuring similarity may affect both the efficiency and quality of clustering solutions. However, there has been no previous comparative study of feature extraction methods used to guide mobile app clustering. Objective In this paper, we investigate different techniques to compute the similarity of apps based on their textual desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The original study extracted features from mobile apps descriptions using four different techniques and compared their effectiveness for clustering apps by using these features and only one clustering approach, i.e. hierarchical clustering [1]. The study found that extracting features using Latent Dirichlet Allocation (LDA) consistently performs well among the investigated feature extraction techniques.…”
Section: Replication Study Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The original study extracted features from mobile apps descriptions using four different techniques and compared their effectiveness for clustering apps by using these features and only one clustering approach, i.e. hierarchical clustering [1]. The study found that extracting features using Latent Dirichlet Allocation (LDA) consistently performs well among the investigated feature extraction techniques.…”
Section: Replication Study Designmentioning
confidence: 99%
“…In order to answer these RQs, we used the same dataset as the original study [1] 3 . This dataset contains 12,664 Android mobile applications belonging to 24 categories, which have been randomly sampled from the Google Play app store.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of large-scale similarity detection based on slightly modified digital fingerprints for Chinese, there is currently no similar research at home and abroad. A. Al-Subaihin [20] proposed a new approach to batch text similarity detection is proposed by combining some ideas from dimensionality reduction techniques and information gain theory. It was focused on search engines need to detect duplicated and near-duplicated web pages.…”
Section: Introductionmentioning
confidence: 99%